2012
DOI: 10.1371/journal.pone.0035653
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Types of Sleep Deprivation on Visual Working Memory Capacity and Filtering Efficiency

Abstract: Sleep deprivation has adverse consequences for a variety of cognitive functions. The exact effects of sleep deprivation, though, are dependent upon the cognitive process examined. Within working memory, for example, some component processes are more vulnerable to sleep deprivation than others. Additionally, the differential impacts on cognition of different types of sleep deprivation have not been well studied. The aim of this study was to examine the effects of one night of total sleep deprivation and 4 night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Some studies have reported differences in behavioral, sleep homeostatic and/or physiological responses to both types of deprivation. 32,176,177 Moreover, only a few experiments have systematically examined the same subjects in both types of deprivation. 167,175,178180 These studies reported inconsistent results, likely due to small sample sizes, different populations, varying doses of sleep restriction, and different outcome measures.…”
Section: Sleep Deprivation and Performancementioning
confidence: 99%
“…Some studies have reported differences in behavioral, sleep homeostatic and/or physiological responses to both types of deprivation. 32,176,177 Moreover, only a few experiments have systematically examined the same subjects in both types of deprivation. 167,175,178180 These studies reported inconsistent results, likely due to small sample sizes, different populations, varying doses of sleep restriction, and different outcome measures.…”
Section: Sleep Deprivation and Performancementioning
confidence: 99%
“…Animal studies suggest that prefrontal D1 receptors sustain the activity of prefrontal neurons while a stimulus is held in memory, and this persistent activity is considered the neural correlate of working memory (Gao et al 2001). At first glance, working memory might be considered a purely waking function; however, working memory performance is improved by prior sleep (Kuriyama et al 2008) and impaired by sleep deprivation (Drummond et al 2012; Hagewoud et al 2010). Sleep may therefore be a useful tool for probing abnormal DA function and working memory in schizophrenia.…”
Section: Neurochemical Abnormalities and Sleep-dependent Plasticitymentioning
confidence: 99%
“…Some studies have reported differences in behavioral, sleep homeostatic and/or physiological responses to chronic partial versus acute total sleep loss [12,15,49]. A few studies have systematically examined the same subjects undergoing both acute total and chronic partial sleep deprivation [14,16-19].…”
Section: Phenotypic Differential Vulnerability To Sleep Lossmentioning
confidence: 99%